Determinação dos parâmetros "elásticos" do solo residual compactado da barragem de Itauba - Guimarães, Roberto Bastos (1977)
Analysis of the stress-strain formulation proposed in 1974 by Corotis, Krizek and Farzin. This formulation is applied mostly to problems in which the principal total stresses (σ1, σ3) increase simultaneously mantaining its ratio constant (σ3/σ1=constant); in another words: it includes the total stress path. In order to do the analysis three UU triaxial test series, with pore pressure measurement, were made, with 9 tests in each; of the nine, in 4 the relation K was mantained constant, varying, however from test to test. The first serie was carried out from specimens trimmed from block samples (undisturbed) of sheep's foot roller compacted trial embakment of Itauba Dam in Rio Grande do Sul State. The second, with the same soil of the same trial embakment, was performed with kneading laboratory compaction, and in the last the specimens were compacted by kneading in Laboratory and tested under "free ends" conditions (lubrificated top and base). The results indicated that: the formulation is satisfactory; the lubrification of the base and top cap has little (maybe negligible) effect on the formulation and on the tests results; there is a strong relation between axial total stress, axial strain, K and effective stress path.